Representasi Visual Dalam Menyelesaikan Masalah Pecahan - Royyan Faradiba; Susiswo Susiswo; Abdur Rahman As’ari (Graduate School of Universitas Negeri Malang, 2019)
Abstract: This study aims to describe the visual representation of grade 5 students in elementary schools in solving fraction problems. The research method used is descriptive qualitative. Data is collected through interviews, recording and student work. The research subjects were 3 students namely those who had high, medium and low mathematical abilities based on the results of the last report card. The results showed that there was no relationship between students 'mathematical abilities and students' visual representation. Students with high mathematical abilities can accurately represent the concept of fractions in the form of a picture but cannot represent the concept of fraction multiplication and compare two fraction numbers into the exact image. Students with moderate and low mathematical abilities cannot represent fraction concepts and multiplication concepts and compare two fraction numbers into image shapes correctly. Based on the results of this study it is expected that the teachers will provide a deeper understanding of the use of visual representation in fraction learning.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan representasi visual siswa kelas V sekolah dasar dalam menyelesaikan masalah pecahan. Metode penelitian yang digunakan adalah kualitatif deskriptif. Data dikumpukan melalui wawancara, perekaman dan pekerjaan siswa. Subjek penelitian berjumlah tiga siswa, yaitu siswa yang memiliki kemampuan matematika tinggi, sedang, dan rendah berdasarkan hasil rapor terakhir. Hasil penelitian menunjukkan bahwa tidak ada hubungan antara kemampuan matematika siswa dengan representasi visual siswa. Siswa berkemampuan matematika tinggi dapat merepresentasikan konsep pecahan ke dalam bentuk gambar dengan tepat, tetapi tidak dapat merepresentasikan konsep perkalian pecahan dan membandingkan dua bilangan pecahan ke dalam bentuk gambar dengan tepat. Siswa berkemampuan matematika sedang dan rendah tidak dapat merepresentasikan konsep pecahan, dan konsep perkalian serta membandingkan dua bilangan pecahan ke dalam bentuk gambar dengan tepat. Berdasarkan hasil penelitian ini diharapkan bagi para guru untuk memberikan pemahaman yang lebih dalam tentang penggunaan representasi visual dalam pembelajaran pecahan.